Answers

2015-10-02T12:20:50+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
P(x)=x²-2√2x+1.
p(2√2)=(2√2)²-(2√2*2√2)+1
p(2√2)=(2√2)²- (2√2)²+1
=0+1.
=1.
Therefore, the answer is 1.

Thank you.
Hope this will help you.
0
even i got the same answer but id ont know how to post
hmm that's fine, do't be suppressed
Pls amrk it as best, if it helped u
otherwise just leave it yaar.
give answer to my question that i have posteddd plessss
2015-10-02T12:22:57+05:30
p ( x ) = x² - 2√2x + 1

p ( 2√2 ) = ( 2√2 )² - ( 2√2 × 2√2 ) + 1

p ( 2√2 ) = ( 8 )  - ( 8 ) + 1 

p ( 2√2 ) = 1
0